2013
DOI: 10.3368/er.31.3.264
|View full text |Cite
|
Sign up to set email alerts
|

Amending Soil with Mulched European Buckthorn (Rhamnus cathartica) Does Not Reduce Reinvasion

Abstract: We conducted a three-year field experiment to determine if amending soils with mulched European buckthorn (Rhamnus cathartica) can limit reinvasion, and whether two methods of incorporation-tilling or surface application-produce similar results. Mulch (a high carbon:nitrogen [C:N] material) may reduce reinvasion by stimulating soil microbial immobilization of N. Converting the woody waste generated during buckthorn removal into mulch would also eliminate both the need to remove this waste from restoration site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…As a result, the number of germinants alive in spring did not differ between mulch depths, and the effects of mulch on buckthorn germinants were transient. These results are similar to those of Iannone et al (), who found mulch to suppress buckthorn only for an 8‐week period, although that period fell fully within the growing season. Despite differences in buckthorn germination rates, it is therefore unlikely that forestry mowing mulch will directly promote or inhibit buckthorn establishment.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As a result, the number of germinants alive in spring did not differ between mulch depths, and the effects of mulch on buckthorn germinants were transient. These results are similar to those of Iannone et al (), who found mulch to suppress buckthorn only for an 8‐week period, although that period fell fully within the growing season. Despite differences in buckthorn germination rates, it is therefore unlikely that forestry mowing mulch will directly promote or inhibit buckthorn establishment.…”
Section: Discussionsupporting
confidence: 91%
“…These combined impacts of buckthorn leave invaded forests with abundant residual propagule pressure from buckthorn with little‐to‐no native species present to resist buckthorn reestablishment (Naeem et al ; Klionsky et al ; Rejmánek ). Therefore, emergence from the seedbank poses a significant threat to forest restoration (Iannone et al ). Management plans following buckthorn removal must account for continued propagule pressure from the seedbank despite the absence of fruiting individuals nearby.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, as illustrated both theoretically (Guo & Symstad, 2008;Catford et al, 2012) and empirically from local to subcontinental scales (Kennedy et al, 2002;Stohlgren et al, 2003), deeper insights can be gained by quantifying and analysing multiple invasion measures [e.g. devising better management practices by detecting varying effects of the same factor on different invader life stages (Iannone & Galatowitsch, 2008;Iannone et al, 2013)].…”
Section: Introductionmentioning
confidence: 99%
“…soil mulch amendments) will not benefit restorations, the latter being confirmed by a recent field experiment (Iannone et al . ). Nonetheless, knowing that buckthorn preferentially establishes in soils having these characteristics can help to develop better focused monitoring programmes, aiding in the prevention of further buckthorn spread.…”
Section: Discussionmentioning
confidence: 97%